Residential cooking-related PM2.5: Spatial-temporal variations under various intervention scenarios. (15th August 2021) - Xiang, Jianbang; Hao, Jiayuan; Austin, Elena; Shirai, Jeff; Seto, Edmund
Abstract: Some cooking events can generate high levels of hazardous PM2.5 . This study assesses the dispersion of cooking-related PM2.5 throughout a naturally-ventilated apartment in the US, examines the dynamic process of cooking-related emissions, and demonstrates the impact of different indoor PM2.5 mitigating strategies. We conducted experiments with a standardized pan-frying cooking procedure under seven scenarios, involving opening kitchen windows, using a range hood, and utilizing a portable air cleaner (PAC) in various indoor locations. Real-time PM2.5 concentrations were measured in the open kitchen, living room, bedroom (door closed), and outdoor environments. Decay-related parameters were estimated, and time-resolved PM2.5 emission rates for each experiment were determined using a dynamic model. Results show that the 1-min mean PM2.5 concentrations in the kitchen and living room peaked 1–7 min after cooking at levels of 200–1400 μg/m 3, which were more than 9 times higher than the peak bedroom levels. Mean (standard deviation) k t for the kitchen, ranging from 0.58 (0.02) to 6.62 (0.34) h −1, was generally comparable to that of the living room (relative difference < 20%), but was 1–5 times larger than that of the bedroom. The range of PM2.5 full-decay time was between 1 and 10 h for the kitchen and living room, and from 0 to >6 h for the bedroom. The PM2.5 emission rates during and 5 min after cooking were 2.3 (3.4) and 5.1 (3.9) mg/min, respectively. Intervention strategies, including opening kitchen windows and using PACs either in the kitchen or living room, can substantially reduce indoor PM2.5 levels and the related full-decay time. For scenarios involving a PAC, placing it in the kitchen (closer to the source) resulted in better efficacy. Highlights: The dispersion of cooking-related PM2.5 throughout a residence was illustrated. The dynamic process of cooking-related PM2.5 levels and emission rates was examined. The impact of various cooking-fume mitigating ways on indoor PM2.5 was evaluated. The PM2.5 emission rates during pan-frying cooking cannot be taken as a constant. Proper measures are needed to reduce the after-cooking emissions.